The National Police's Efforts to Eradicate Thuggery Offences (A Law Study) - M. Qahar Awaka; Wiend Sakti Myharto (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Thuggery has increased in recent years as a result of numerous segments of the community members who were unable to perceive economic well-being, such as other community members. Street crime and crime (Street Crime) are grassroot crimes that actually worry tiny people, which is why law enforcement officials, particularly the National Police, require them. The researcher's definition of the issue is as follows: What is the form of legal protection against thuggery actions in Indonesia? And how is the effort to overcome the crime of thuggery in Indonesia? The researcher's study method is a normative juridical one, which entails analyzing the relationship between applicable laws, legal theories, and the practice of implementing positive law in relation to the issues covered.